Formulation and characterization of beeswax/rosemary oil nanostructured lipid carrier for drug delivery system / Farhanim Mohd Latif - Farhanim , Mohd Latif (2021)
A stable colloidal suspension of nanostructured lipid carriers (NLCs) was synthesized from natural source of lipid. The toxicity and insolubility of drugs in water remain a significant problem and has led to the development of food-grade drug delivery systems such as nanostructured lipid carriers (NLCs). NLCs composing various amount of beeswax (BW), rosemary oil (RO) and poloxamer 188 (P188) were prepared by melt-emulsification combined with ultrasonication method. The physicochemical properties of NLC also were determined. Optimization of the formulation (F) was performed based on the criteria of stability. Formulation with the smallest particle size and highest magnitude of zeta potential was selected to be loaded with terbinafine hydrochloride (TBHC1) and hydrophilic molecule, which is calcein. Drug separation methods that applied in this study were centrifugal ultrafiltration and size exclusion chromatography method. The percentage of encapsulation efficiency, drug loading efficiency and drug release were evaluated. The optimized formulation composing 3.75 % BW, 1.25 % RO, 3 % P188 and 92 % deionized water. The mean of particle size and zeta potential for optimize NLC were (174  2) nm and (-36  5) mV, respectively. By using x-ray diffractometer (XRD) and differential scanning calorimeter (DSC), the optimized formulation of NLC showed a lower degree of crystallinity and melting enthalpy compared to solid lipid nanoparticle (SLN) of BW. The morphology of NLC was observed as spherical shape with a dense appearance in the transmission electron microscope (TEM) images. The encapsulation efficiency and loading efficiency were found dependent on the amount of TBHCl and calcein. The release of TBHC1 and calcein from the optimized formulation were (62.87± 0.04) % and (41.70 ± 0.09) % respectively. It can be concluded that NLC prepared from natural source of lipid may serve as a potential carrier for drug delivery.